Extension of Technology Acceptance Model (Etam): Adoption of Cryptocurrency Online Trading Technology - Agustina, Duwi (Jurnal Ekonomi, 2019)
The main idea of the study was to determine the influence of the antecedents (trialability and compexity) on the existing constructs of Technology Acceptance Model (TAM) and to test measurement invariance on the relationship between the latent constructs used in this extended version of Technology Acceptance Model (ETAM). A survey questionnaire was administered on Cyptocurrency mobile applicantions users and a total of 41 responses were collected. The research model was assessed using SEM-PLS approach. The structural model was then tested in order to establish validity & reliabelity. The invariance test was first performed on the measurement model and then on the structural model using SmartPLS 3.0. The predictor variables in ETAM were able to explain 44,9% of the variance in actual usage of Cryptocurrency mobile applications.